Sudden death amongst people practicing competitive sports (Review Article) - Bartłomiej Wrzesiński; Edyta Piechocka; Grzegorz Duda; Paweł Wojtczak (Kazimierz Wielki University, 2018)
Sudden cardiac death is and unexpected cardiac arrest that may occur both during exercise and also an hour after its completion. It most often occurs in young sportsmen under 35 years of age and is usually associated with improperly performed physical activity proceeded by lack of specialized medical examination and research. Natural and cardiac causes are two basic phenomena that lead to cardiac death. As confirmed by Framingham Heart Study, conducted in the eighties of the twentieth century on the population of Americans, natural causes accounted for 13% while cardiac causes accounted for 88% off all. The statistics of the largest centers of sport medicine are presented as follows: Germany - 1 death per 200,000 people practicing sports (total) while United States of America - 1 death per 80,000 people per year. The problem of of sudden deaths is and important topic worthy of a broader and more specific analysis. It should be noted that physical exertion is not is not a direct cause of sudden deaths. Currently the most research concerns professional athletes who have extensive support and knowledge about the exercise they perform. The main problem concerning subject of sudden deaths are not diagnosed hearth defects. <> Additional topic of interest is rarity of medical tests performed by amateur athletes and athletes at the lower levels of competition. Such athletes do not  have as extensive knowledge as their experienced idols, which may bring tragic consequences.